Pierwszy raport zbiorczy dla Józefa Stalina z „operacji polskiej” - Sommer, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The paper includes the first summary report compiled for Joseph Stalin from the “Polish Operation,” i.e. the genocide undertaken against the Polish people in the Soviet Union during the 1937–1938 period, coming from the Central Archive of the Federal Security Service, located in Moscow. The report has been compiled at the beginning of September 1937 in the office of Nicolai Jezow, the then chief of the People’s Commissariat for Internal Affairs NKVD, and constitutes a compilation of the information flowing to Lubyanka on the planned murder of Poles in the respective regions of the Soviet Union, prepared by relevant administrative cells of the NKVD. The document is the earliest account of the crime and registers the first ten days of this process. It is the first publication of this document in Polish.
Keywords: Stalin, Józef (1878-1953); ludobójstwo; NKWD; Ežov, Nikolaj Ivanovič; „operacja polskiej”